👤

when x=(-2) 7x^2-4x+3

Sagot :

Answer:

x=

−5

28

+

1

28

√193 or x=

Step-by-step explanation:

Let's solve your equation step-by-step.

x=((−2)(7))(x2)−4x+3

Step 1: Simplify both sides of the equation.

x=−14x2−4x+3

Step 2: Subtract -14x^2-4x+3 from both sides.

x−(−14x2−4x+3)=−14x2−4x+3−(−14x2−4x+3)

14x2+5x−3=0

For this equation: a=14, b=5, c=-3

14x2+5x+−3=0

Step 3: Use quadratic formula with a=14, b=5, c=-3.

x=

−b±√b2−4ac

2a

x=

−(5)±√(5)2−4(14)(−3)

2(14)

x=

−5±√193

28

x=

−5

28

+

1

28

√193 or x=

−5

28

+

−1

28

√193